PHOTOTHERMAL EFFECT OF GOLD NANOSHELLS IN TISSUE - Thùy Dương, Vũ Thị; Thương, Trịnh Thị; Dương, Vũ; Thùy, Nguyễn Thị; Hà Liên, Nghiêm Thị; Hòa, Đỗ Quang; Nhung, Trần Hồng (Vietnam Journal of Science and Technology, 2016)
This work presents the research results on photothermal effect caused by gold nanoshells Fe3O4/SiO2/Au and SiO2/Au in tissue under illumination of a diode laser continuous light at 808 nm. The results shown that the average temperature of samples injected with 1x108 SiO2/Au and Fe3O4/SiO2/Au nanoshells reach to 58° ± 5°C and 50° ± 5°C, respectively. This temperature can induce the irreversible damage to tissue. The photothermal transduction efficiency h of Fe3O4/SiO2/Au and SiO2/Au shells was determined as 16 % and 22 %, respectively. This study proves that gold nanoshells can be used to destroy the tumor cells by photothermal effect.